Dakwah Menyikapi Fenomena Pencucian Uang Hasil Korupsi - Syuhada . (Alhadharah: Jurnal Ilmu Dakwah, 2017)
Corrupt politicians who sometimes seems generous is a phenomenon, because the corrupt deeds are evil deeds that are the opposite of generosity which is a good deed. Given that corruption is a secret evil of the actors, they tend cover it up in their own ways. Their efforts take in the form of money laundering by donating some of their corrupt wealth to religious social institutions. Such efforts are considered to disguise the corrupt gains and to create a self-image as a philanthropist as well as hope of God's forgiveness. Such phenomenon is believed to occur due to the limited understanding of religious teachings, both by the perpetrators of corruption as donators and social and religious institutions as recipients. Dakwah should respond to this phenomenon. The parties are assessed as likely perpetrators of corruption are given the guidance to repent properly, while the religious social institutions are guided to be aware of the donations accepted.